The neuropeptide Drosulfakinin regulates social isolation-induced aggression in Drosophila. - Agrawal, P.; Kao, D.; Chung, P.; Looger, L.L. (Journal of Experimental Biology, 2020)
Social isolation strongly modulates behavior across the animal kingdom. We utilized the fruit fly Drosophila melanogaster to study social isolation-driven changes in animal behavior and gene expression in the brain. RNA-seq identified several head-expressed genes strongly responding to social isolation or enrichment. Of particular interest, social isolation downregulated expression of the gene encoding the neuropeptide Drosulfakinin (Dsk), the homologue of vertebrate cholecystokinin (CCK), which is critical for many mammalian social behaviors. Dsk knockdown significantly increased social isolation-induced aggression. Genetic activation or silencing of Dsk neurons each similarly increased isolation-driven aggression. Our results suggest a U-shaped dependence of social isolation-induced aggressive behavior on Dsk signaling, similar to the actions of many neuromodulators in other contexts.